Photo‐Induced Microfluidic Production of Ultrasmall Glyco Gold Nanoparticles. Issue 1 (29th November 2022) - Perez Schmidt, Patricia; Pagano, Katiuscia; Lenardi, Cristina; Penconi, Marta; Ferrando, Ruth Mateu; Evangelisti, Claudio; Lay, Luigi; Ragona, Laura; Marelli, Marcello; Polito, Laura
Abstract: Ultra‐small gold nanoparticles (UAuNPs) are extremely interesting for applications in nanomedicine thanks to their good stability, biocompatibility, long circulation time and efficient clearance pathways. UAuNPs engineered with glycans (Glyco‐UAuNPs) emerged as excellent platforms for many applications since the multiple copies of glycans can mimic the multivalent effect of glycoside clusters. Herein, we unravel a straightforward photo‐induced synthesis of Glyco‐UAuNPs based on a reliable and robust microfluidic approach. The synthesis occurs at room temperature avoiding the use of any further chemical reductant, templating agents or co‐solvents. Exploiting 1 H NMR spectroscopy, we showed that the amount of thiol‐ligand exposed on the UAuNPs is linearly correlated to the ligand concentration in the initial mixture. The results pave the way towards the development of a programmable synthetic approach, enabling an accurate design of the engineered UAuNPs or smart hybrid nano‐systems. Abstract : We propose a robust, fast and green synthetic route to produce ultrasmall glyco gold nanoparticles (glyco‐UAuNP) by an innovative photo‐induced microfluidic approach. The absence of templating and reducing agents allows a simple product purification and the recovery of the unbound thiol‐ligand. We successfully built a glyco‐UAuNP library, testing different combinations of linker/sugar and shaping the UAuNP glyco‐ligand density.